The answer to this problem is equal to the absolute value of one less than the answer to this problem.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Woah!! I thought it was a troll!
I'm stupid enough to not see this. :(
This question brings back memories of the second problem I ever contributed .
Log in to reply
Which brings back memories of where I was when I solved it. I was in New Delhi, India, sitting on a sofa, right after Brilliant made that change in format. I was watching Glee on TV and eating butter naan.
great
Ohh missed it!!
yeah, did the same!!
nice sir
That is fabulous!!
Why is the problem rated 1899? :-o
How did u get ∣ x − 1 ∣ = x ?? The problem does not mention the absolute value of 1 less than the answer to the problem equals the answer.... :\
Log in to reply
Naturally the answer you give to that question is the answer, the same "answer" used in the question.
Log in to reply
Oh...you're very correct...I feel like an idiot now....
Let the answer be x .
So ∣ x − 1 ∣ = x
( x − 1 ) 2 = x 2
x 2 − 2 x + 1 = x 2
− 2 x + 1 = 0 ⇒ x = 2 1
I did it same way nice solution
Did the same way and got it exactly right
X = |1-X| X = 1-X OR X = -1+X (WHICH IS NOT POSSIBLE) 2X = 1 X = 1/2 = 0.5
x=|x-1| => x=0.5
Let the answer be x.
We have x=|x-1|.
If x-1>0, we have x=x-1, which is clearly impossible. And x=0 doesn't work. If x-1<0, we have x=-x+1, so x=.5 is our answer.
Here is my solution to this problem : Let x=answer
x=lx-1l
square both sides of the equation
x2=x2 - 2x + 1 2x = 1 x = 0.5
Problem Loading...
Note Loading...
Set Loading...
Great problem! Let the answer be x . Thus, ∣ x − 1 ∣ = x . It is obvious that the points that satisfy this equation are one away from each other and have 0 as their axis of symmetry. From this, the answer is obviously 0 . 5 . It is much more rigorous to proceed as following, however.
Case 1: x − 1 is positive. Thus x − 1 = x which is impossible.
Case 2: x − 1 is negative, in which case it reverses as 1 − x . Solving, 1 − x = x ⟹ 2 x = 1 ⟹ x = 0 . 5 .